Evidence-based risk factors for major complications during Ramadan fasting in people with diabetes grouped under IDF-DAR risk categories. (March 2022) - Rahmatullah,; Ahmedani, Muhammad Yakoob; Basit, Abdul; Zia, Shagufta; Hasan, Imran; Masroor, Qazi; Shaikh, Abrar; Khan, Jehangir; Iqbal, Waheed
Abstract: Aim: To identify evidence-based risk factors for major complications during Ramadan fasting in people with diabetes grouped under IDF-DAR risk categories. Methods: This prospective observational multicenter study was conducted by Baqai Institute of Diabetology and Endocrinology (BIDE) between April-June 2019. People with diabetes having intention to fast during Ramadan were recruited. Demographic data collection along with risk categorization was done during pre-Ramadan visit. Structured education was given on one- to-one basis to each of the study participants. Assessment of complications was done during post Ramadan visit. Results: A total of 1045 people with diabetes participated with near equal gender distribution. Two thirds of study population was grouped into very high- and high-risk categories. Frequencies of major hypoglycemia, major hyperglycemia, hospitalization & need to break the fast were 4.4%, 10.8%, 0.8% & 3.1% respectively. On multivariate analysis, the risk factors found for major hypoglycemia during Ramadan were male gender, use of sedatives & antidepressants & having type1 diabetes mellitus, history of DKA/HHS during last 3 months for major hyperglycemia, major hypoglycemia & hospitalization for breaking of fast while older age, acute illness, and major hypoglycemia were identified factors for hospitalization. Conclusion: In this prospective study evidence-based risk factors for fasting related major complications were identified in people with diabetes. It is imperative to recognize these factors during pre-Ramadan risk assessment visit.